2008
DOI: 10.1677/joe-08-0043
|View full text |Cite
|
Sign up to set email alerts
|

Stanniocalcin 2 expression is regulated by hormone signalling and negatively affects breast cancer cell viability in vitro

Abstract: Stanniocalcin 1 (STC1) and STC2 are secreted, homodimeric glycoproteins that share 30% amino acid sequence identity. Breast tumour gene profiling studies have demonstrated significantly upregulated STC2 expression in hormoneresponsive positive breast tumours; therefore, the purpose of this study was to investigate STC2 hormonal regulation and function in breast cancer cells. Here we report that STC2 is expressed in a number of human breast cancer cell lines, regardless of their oestrogen (E 2 ) and progesteron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 59 publications
(69 reference statements)
3
60
0
1
Order By: Relevance
“…29 Additionally, it was reported that STC2 expression was sporadically abrogated in human cancer cells by transcriptional silencing associated with CpG island promoter hypermethylation. 36 Constitutive expression of human STC2 in transgenic mice acts as a potent growth inhibitor in vivo and results in a significant reduction of intramembranous and endochondral bone development, as well as high neonatal morbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Additionally, it was reported that STC2 expression was sporadically abrogated in human cancer cells by transcriptional silencing associated with CpG island promoter hypermethylation. 36 Constitutive expression of human STC2 in transgenic mice acts as a potent growth inhibitor in vivo and results in a significant reduction of intramembranous and endochondral bone development, as well as high neonatal morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the STC1 gene is associated with some cancers. [17][18][19][20][21][22][23][24] STC2 was reported to be associated with breast cancer, [25][26][27][28][29] ovarian cancer 30 and renal cell carcinoma. 31 However, the relationship between STC2 expression and clinicopathological factors in colorectal cancer has not yet been investigated.…”
mentioning
confidence: 99%
“…The EGPs were pooled for each genotype from a particular litter for RNA extraction or protein lysates which were generated by homogenization in lysis buffer and protein concentration was determined using a Bradford assay (BioRad) (Raulic et al 2008). Western blot analysis was performed as described previously using 50 lg protein per lane, probed with PCNA antibody (Cell Signaling #2586), or cleaved caspase-3 (Asp175) antibody (Cell Signaling #9661) followed by probing with antibody against b-actin as a loading control (Sigma A2066) (Raulic et al 2008). The positive control lysate for apoptosis and detection of cleaved caspase-3 fragments was generated by an overnight treatment of primary mouse ovarian cells in culture with cycloheximide (50 lg/ml).…”
Section: Skeletal Staining and Histologymentioning
confidence: 99%
“…4b). The concentration employed to inhibit ER has been defined in numerous reports [Chambliss and Shaul, 2002;Barnett et al, 2008;Raulic et al, 2008]. Exposure of cells to 100 nM of fulvestrant alone did not significantly modify the gene expression level of b3-tubulin or PS2.…”
Section: B3-tubulin Mrna Regulation Is Er Dependentmentioning
confidence: 99%